Pertumbuhan dan Hasil Jagung Manis pada Berbagai Takaran Biochar yang Dibudidayakan di Musim Kemarau - Salawati Salawati; Sjarifuddin Ende (Universitas Gadjah Mada, 2026)
Rice husk biochar has the potential to enhance the growth of sweet corn plants during the dry season due to its water-holding capacity, high organic-C and CEC (Cation Exchange Capacity) content, and its ability to improve soil biological quality. This research was conducted with the main objective of testing the effect of rice husk biochar application on the agronomic characteristics of sweet corn grown on a farmer's field in Togaso village, Galang District, Tolitoli Regency, Central Sulawesi, during the dry season. The study employed a Randomized Block Design (RBD) with four treatment levels and four replications, namely b0 (0 tons ha-1), b1 (5 tons ha-1), b2 (10 tons ha-1) and b3 (15 tons ha-1) biochar. The results of the study showed that the application of rice husk biochar had a significant effect (p<0.05) on the observed parameters, namely the increase in plant height, number of leaves, stover dry weight (or: shoot dry weight), Leaf Area Index (LAI), fresh cob weight with and without husks, and production per hectare, but had no effect on the Net Assimilation Rate (NAR) parameter of sweet corn plants in the dry season.